Eksistensi ‘Illat dalam Mengukuhkan Teks Hadis-hadis Ru’yat al-Hilāl dan Fungsinya dalam Pengembangan Hukum Islam - Busyro Busyro (Al-Ahkam, 2018)
Ḥisāb and ru’yat always be warm conversations when there is an early determination of Ramadhan and Shawwal. At that time, there are always two camps of scholars in reacting, the scholars who hold on to ḥisāb (calculating the calendar) on one side, and on the other hand hold to ru’yat al-hilāl (seeing the moon directly). This in turn often leads to time differences in setting the beginning of the month among Muslims. With the aim to unite the people in starting their worship, some scholars try to understand the texts of these traditions about ru’yat al-hilāl by trying to find the 'illat (reason) of the laws of hadiths about ru’yat al-hilāl. Their study of the 'illat law resulted in the conclusion that the ru’yat al-hilāl is only a suitable means for the people that time and may not suitable for Muslims in this modern era. Therefore Muslims must use other wasīlah (means) which further guarantee the realization of the purpose of law, namely modern astronomy. The conclusion of the law from the side of the discovery of ‘illat seems to be less suited to the purpose of ta'līl al-aḥkām, is to establish textual texts in addition to discovering the forms of development of the texts.